2022
DOI: 10.1155/2022/7276670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3-Nitroacetophenone on Corrosion Inhibition of Mild Steel in Acidic Medium

Abstract: Acetophenone derivatives are eco-friendly corrosion inhibitors to prevent corrosion of mild steel (MS) in acidic medium. In this work, the inhibition effect of 3-nitroacetophenone (3-NA) on the corrosion of MS in acidic medium (1 N HCl) was investigated using weight loss measurements, electrochemical measurements, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and quantum chemistry analysis. The studies were performed using different concentrations of inhibitors and at different temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…From the plot of ln 𝐶. 𝑅 Vs 1/T Fig ( 4), activation parameters like activation energy (Ea) were calculated and are listed in Table (3). From Fig ( 4) a linearity is observed between ln 𝐶. 𝑅 and 1/T indicates the consistency in the data obtained.…”
Section: Activation Parametersmentioning
confidence: 82%
See 3 more Smart Citations
“…From the plot of ln 𝐶. 𝑅 Vs 1/T Fig ( 4), activation parameters like activation energy (Ea) were calculated and are listed in Table (3). From Fig ( 4) a linearity is observed between ln 𝐶. 𝑅 and 1/T indicates the consistency in the data obtained.…”
Section: Activation Parametersmentioning
confidence: 82%
“…The values of (𝛥G) calculated are listed in Table (3). From the data obtained it was observed that the values of (𝛥G) were positive and increased as the temperature and concentration increased.…”
Section: Srnomentioning
confidence: 97%
See 2 more Smart Citations